Evaluation of Nanoemulsion of Eucalyptus globulus Oil as Potent Botanical Larvicide Against Malaria Vector , Anopheles stephensi and West Nile Vector, Culex pipiens Under Laboratory and Semi-field Conditions - Sara Sabzalizade; Amir Amani; Hassan Vatandoost; Fatemeh Hosseini; Roya Najafi-Taher; Hamid Reza Basseri (Journal of Arthropod-Borne Diseases, 2022)
Objectives Due to undesired environmental impact of insecticides as well as resistant of vectors to them, development of organic and natural insecticides have been more considered. In the current study, we developed nanoemulsion of eucalyptus and investigated lavicidal activity of it against malaria vector, Anopheles stephensi and Culex pipiens under  laboratory as well as semi field conditions.